2022
DOI: 10.1002/zamm.202100560
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aspect of boron nitride nanotubes (BNNT) and multiwall carbon nanotubes (MWCNT) with distinct physical features: Keller Box simulations

Abstract: The research on hybrid nanofluid has been focused by researchers widely in the current decade. Being the combination of two distinct nanoparticles, the researchers have predicted the thermal efficiencies of hybrid nanofluid model in view of distinct nanoparticles. However, the no attention is devoted by researchers towards the thermal mechanism of hybrid nanofluid with boron nitride nanotubes (BNNTs) and multiwall carbon nanotubes (MWCNTs) with distinct impressive characteristics. This communication aims explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Subspaces exist for U * , V * , and θ * , and Q = L 2 (Ω) is the test space for pressure. The weak form of the governing equations [17][18][19][20] is provided as:…”
Section: Weak Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subspaces exist for U * , V * , and θ * , and Q = L 2 (Ω) is the test space for pressure. The weak form of the governing equations [17][18][19][20] is provided as:…”
Section: Weak Formulationmentioning
confidence: 99%
“…It was found that the use of an elastic fin and CNT led to an increase in the Nusselt number. Farooq et al [19] performed simulations using the Keller Box method to study the thermal behavior of BNNT and MWCNT nanofluids' convective flow.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the action of Lorentz force is also incorporated in the mathematical model. Apposite mathematical relations/symbols have been acted to renovate the leading equations into a dimensionless system, and then, numerical simulation is made via the Keller-Box method [35][36][37]. Finally, the chief results obtained through the current mathematical study are presented via different graphs/tables.…”
Section: Introductionmentioning
confidence: 99%